RESOLVING DATABASE CONSTRAINT COLLISIONS USING IIS*CASE TOOL - Ristić, Sonja; Luković, Ivan; Pavićević, Jelena; Mogin, Pavle (Journal of Information and Organizational Sciences, 2007)
Integrated Information Systems*Case (IIS*Case) R.6.21 is a CASE tool that we developed to support automated database (db) schema design, based on a methodology of gradual integration of independently designed subschemas into a database schema. It provides complete intelligent support for developing db schemas and enables designers to work together and cooperate reaching the most appropriate solutions. The process of independent design of subschemas may lead to collisions in expressing the real world constraints and business rules. IIS*Case uses specialized algorithms for checking the consistency of constraints embedded in the database schema and the subschemas. IIS*Case supports designers in reviewing and validating results obtained after each step of the design process. The paper outlines the process of resolving collisions. A case study based on an imaginary production system is used to illustrate the application of IIS*Case. Different outcomes and their consequences are presented.